Die Bezugsnormen wertender Satzadverbien in Texten gesprochener Sprache - Schatte, Christoph (Uniwersytet im. Adama Mickiewicza, 1995)
The article presents the division of sentential adverbs depending on their connection with: 1) logical value of sentence, 2) scope of sentence value, 3) relevance of content, 4) division of text and 5) evaluating statements, and then argues with paraphrasing as the method of explaining meaning and function. The author proposes using different connections of sentential adverbs as the criterion of the choice of means of explanation. This classification allows to precisely define the various norms of reference of qualifying sentential adverbs.